Edmond Locard — “Father of the Crime Lab” - Balláné Füszter, Erzsébet (Magyar Rendészet, 2016)
Forensic science has contributed to our world a great deal. Edmond Locard was a real criminalist in the classic sense who had a paramount role in the European and worldwide development of criminalistics, the practice of gathering evidence for scientific examination and crime solving. In 1910, Locard was able to convince the police of Lyon to establish the first crime laboratory for collecting and examining evidence from crime scenes.